Rethinking relationships with nature: human – wetland connections in Marlborough, Harare, Zimbabwe - Sigauke, Esther (Social Anthropology, 2023)
This thesis is an ethnographic study of the intricate relationship between humans and the wetland in Marlborough, Harare. It focuses primarily on poor urban farmers and the wetland environment in which their activities are criminalised. Data were collected by means of interviews, observations and design thinking-augmented focus group discussion. The thesis problematises the notion of criminalising urban agriculture on wetlands by exploring the underlying factors that push the farmers to engage in practices deemed illegal. The analysis is done in relation to other stakeholders, such as property developers – who, despite causing more harm to the wetland, navigate their way to implement their activities. This raises ethical questions on the selective application of the law, as the elite and those connected to the people yielding power use the wetland as they wish, but poor farmers striving to earn a living find themselves at the receiving end of the law. This invokes issues of democracy, capitalism, social justice and the legacy of colonialism. It emerged in the study that the farmers are strongly connected to the wetlands as the source of their livelihoods. Although they have no property rights and take the risk of farming on the wetlands, they are not criminals. A harsh economic environment, characterised by unemployment and negligible income, makes them dependent on the wetland for their livelihoods. They use simple tools for farming that do not cause harm to the environment, and they apply farming methods that are compatible with conservation ethics. Their main challenge is that they do not contribute to economic development as measured by the gross domestic product, so their voices are not heard when decisions are made, and they fall into line with decisions made in a top-down manner. Accordingly, this thesis positions the conflict between the wetland farmers and other stakeholders as an interplay of power dynamics. When such a situation unfolds, the poor farmers bear the full brunt of the law in an uneven playing field, further condemning them to extreme poverty in an environment with no safety nets. The study used an innovative and hybrid method of public engagement, using design thinkingaugmented focus group discussion. Being human-centred and empathetic to the users, the method was instrumental in engaging poor farmers in the design and implementation of customised solutions to their problems. Several solutions were generated, tested and iterated to meet the underlying needs of the users and a win-win situation for the farmers and the wetland emerged, suggesting that a humanistic approach to environmental management has the potential to produce desirable results. The study recommends that future scholarship focus on how to disentangle capitalism and ensure that control and ownership of the environment is not left in the hands of private owners for profit, but that the state puts checks and balances in place to cater for marginalised and underserved communities.